A mammoth undertaking: harnessing insight from functional ecology to shape de‐extinction priority setting. (12th September 2016) - McCauley, Douglas J.; Hardesty‐Moore, Molly; Halpern, Benjamin S.; Young, Hillary S.
Summary: De‐extinction, or the process of resurrecting extinct species, has been advanced as a promising new tool in conservation biology. Most scientific discussion of de‐extinction has thus far focused on the methodology and ethics of bringing once‐extinct species back to life. We ask: How can de‐extinction be strategically shaped into a service that maximally benefits ecological communities and ecosystems? Ecologists often indicate that the worst facet of extinction is the associated loss of ecological function. Several decades of research on defining, classifying and tracking changes in portfolios of ecological function have generated a rich repository of information that should be mined to help guide de‐extinction towards a future where its products can meaningfully restore extinction‐induced loss of function. Classifications of ecological function remain more subjective than other biological taxonomies. Yet, there is a clear consensus among ecologists that the functions of certain species are less ecologically redundant than others. The loss of such functionally unique species can have proximate and cascading effects on community and ecosystem functioning. We review, from an ecologist's vantage point, efforts underway to use de‐extinction to resurrect the woolly mammoth and the passenger pigeon. These iconic case studies illustrate the opportunities and challenges ahead for restoring ecological function using de‐extinction. There is great risk that de‐extinction could limit itself to the fabrication of products that mimic the biology of extinct species, but fail to resurrect their ecology. We suggest three ways that de‐extinction may more meaningfully restore the functioning of once‐extinct species: (i) select target species from guilds with low functional redundancy; (ii) concentrate on species that went extinct recently rather than older extinctions; and (iii) only work with species that can be restored to levels of abundance that meaningfully restore ecological function. A lay summary is available for this article. Abstract : Lay Summary